Sistem Pengambilan Keputusan Kepuasan Pelanggan Bengkel Motor Berkah dengan Metode Simple Additive Weigthing - Dedi Mahrizon (JURIKOM (Jurnal Riset Komputer), 2022)
Berkah Motor Workshop is a form of service in motorcycle repair activities, both minor and major damage. Bengkel Berkah strives to provide the best service so that customers feel fast after getting the results of the repair services provided by the blessing workshop. Consumer satisfaction is the main factor in providing services and is able to provide satisfaction for every customer, so that every customer feels satisfied and happy with the services that have been provided. Simple Additive Weighting (SAW) method by finding the weighted sum of the performance of each alternative on all attributes. The final result of this research is a decision-making system in determining customer satisfaction from the results of the Berkah Motor Workshop in accordance with the highest value assessment of the resulting output. Determination of customer satisfaction can be assessed from 5 aspects, namely service, performance, results, responsibility and price. The highest output value is obtained with the highest value, namely 1 on behalf of R and the smallest value of 0.665 on behalf of consumers N and A. The decision-making system using the simple additive weighing method is able to solve problems regarding the assessment of consumer satisfaction in the decision-making system